Sentiments and Activities : Essays in social science - "Homans, George Casper" (Glencoe, 1962)
This book contains following topics: Autobiographical Introduction; The small Warship; Status among Clerical Workers; The cash posters; Status Congruence; The Sociologists Contribution to managements in the future; Giving a Dog a bad name; Bureaucracy as big big brother; Men and the land in the middle Ages; The rural sociology of Medieval England; The frisians in east Anglia; small groups.
Keywords: Sociology